The structure of VgrG1 fromPseudomonas aeruginosa Pseudomonas aeruginosa, the needle tip of the bacterial type VI secretion system. Issue 1 (1st January 2016) - Spínola-Amilibia, Mercedes; Davó-Siguero, Irene; Ruiz, Federico M.; Santillana, Elena; Medrano, Francisco Javier; Romero, Antonio
Abstract : This article presents the crystal structure of full‐length VgrG1 from P. aeruginosa P. aeruginosa, a component of the type VI secretion‐system machinery essential in bacterial infection. Abstract : The type VI secretion system (T6SS) is a mechanism that is commonly used by pathogenic bacteria to infect host cells and for survival in competitive environments. This system assembles on a core baseplate and elongates like a phage puncturing device; it is thought to penetrate the target membrane and deliver effectors into the host or competing bacteria. Valine–glycine repeat protein G1 (VgrG1) forms the spike at the tip of the elongating tube formed by haemolysin co‐regulated protein 1 (Hcp1); it is structurally similar to the T4 phage (gp27)3 3 –(gp5)3 3 puncturing complex. Here, the crystal structure of full‐length VgrG1 from Pseudomonas aeruginosa Pseudomonas aeruginosa is reported at a resolution of 2.0 Å, which through a trimeric arrangement generates a needle‐like shape composed of two main parts, the head and the spike, connected via via a small neck region. The structure reveals several remarkable structural features pointing to the possible roles of the two main segments of VgrG1: the head as a scaffold cargo domain and the β‐roll spike with implications in the cell‐membrane puncturing process and as a carrier of cognate toxins.